Demonstration of Multi Pump Wide Gain Raman Amplifiers for Maximization of Repeaters Distance in Optical Communication Systems - Ahmed Zaki Rashed (Institute of Advanced Engineering and Science, 2015)
Fiber Raman amplifiers in ultra wide wavelength division multiplexing (UW-WDM) systems have recently received much more attention because of their greatly extended bandwidth and distributed amplification with the installed fiber as gain medium. It has been shown that the bandwidth of the amplifier can be further increased and gain spectrum can be tailored by using pumping with multiple wavelengths. Wide gain of the amplifier is considered where two sets of pumps NR 5,10 are investigated. The gain coefficient is cast under polynomial forms. The pumping wavelength lR is over the range 1.40 £ lR, mm £ 1.44 and the channel wavelength ls is over the range 1.45 £ ls, mm £ 1.65. Two multiplexing techniques are processed in long-haul transmission cables where number of channels is up to 10000 in ultra-wide wavelength division multiplexing (UW-WDM) with number of links up to 480. The problem is investigated over wide ranges of affecting sets of parameters.